Antitumour activity of neratinib in patients with HER2-mutant advanced biliary tract cancers - Harding, James J.; Piha-Paul, Sarina A.; Shah, Ronak H.; Murphy, Jessica J.; Cleary, James M.; Shapiro, Geoffrey I.; Quinn, David I.; Braña, Irene; Moreno, Victor; Borad, Mitesh; Loi, Sherene; Spanggaard, Iben; et al. (Nature communications, 2023)
HER2 mutations are infrequent genomic events in biliary tract cancers (BTCs). Neratinib, an irreversible, pan-HER, oral tyrosine kinase inhibitor, interferes with constitutive receptor kinase activation and has activity in HER2 -mutant tumours. SUMMIT is an open-label, single-arm, multi-cohort, phase 2, ‘basket’ trial of neratinib in patients with solid tumours harbouring oncogenic HER2 somatic mutations (ClinicalTrials.gov: NCT01953926). The primary objective of the BTC cohort, which is now complete, is first objective response rate (ORR) to neratinib 240 mg orally daily. Secondary objectives include confirmed ORR, clinical benefit rate, progression-free survival, duration of response, overall survival, safety and tolerability. Genomic analyses were exploratory. Among 25 treatment-refractory patients (11 cholangiocarcinoma, 10 gallbladder, 4 ampullary cancers), the ORR is 16% (95% CI 4.5–36.1%). The most common HER2 mutations are S310F (n = 11; 48%) and V777L (n = 4; 17%). Outcomes appear worse for ampullary tumours or those with co-occurring oncogenic TP53 and CDKN2A alterations. Loss of amplified HER2 S310F and acquisition of multiple previously undetected oncogenic co-mutations are identified at progression in one responder. Diarrhoea is the most common adverse event, with any-grade diarrhoea in 14 patients (56%). Although neratinib demonstrates antitumour activity in patients with refractory BTC harbouring HER2 mutations, the primary endpoint was not met and combinations may be explored. In biliary tract cancer HER2 alterations correlate with poor prognosis. Here, the authors present the results of a phase II clinical trial reporting the efficacy and safety of the tyrosine kinase inhibitor neratinib in patients with HER2-mutation positive advanced biliary tract cancers.